Pengaruh Efektifitas Kerja terhadap Disiplin Kerja dalam Organisasi - Sri Yulianty Mozin; Alfiyah Agussalim; Mohamad Rasya Mohi; Nazlih Alhusna Abas; Risnawati R. Itani; Nur Ramadani Karim; Alfika Yope; Mutiara Take (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2026)
This study is motivated by the importance of work effectiveness as a key indicator of organizational success in facing an increasingly complex and competitive work environment. Work discipline is viewed as one of the critical factors that can support the achievement of optimal work effectiveness. This study aims to analyze the relationship between work discipline and work effectiveness and to identify the factors influencing them within an organizational context. The method used is a Systematic Literature Review, which involves examining various relevant scientific articles through the stages of identification, selection, evaluation, and data synthesis. The results of the study indicate that work discipline plays a significant role in enhancing work effectiveness through adherence to rules, punctuality, responsibility, and consistency in task execution. Furthermore, work effectiveness can also foster the development of discipline through structured work systems and clear operational standards. The relationship between these two variables is reciprocal and influenced by factors such as leadership, organizational culture, motivation, human resource competencies, and the utilization of technology. The implications of this research underscore the importance of integrating work discipline and organizational systems to sustainably enhance work effectiveness.